Hypoprolactinemia as a Clue to Diagnosis of Mild Central Hypothyroidism due to IGSF1 Deficiency - Anastasios Papadimitriou; Anna Papadopoulou; Kleanthis Kleanthous; Dimitrios T. Papadimitriou; Vassiliki Papaevangelou (Galenos Yayincilik, 2020)
Loss-of-function mutations of IGSF1 are an X-linked cause of central hypothyroidism (CeH) and hypoprolactinemia. A boy who is now 15.2 years old presented at the age of 7.69 years for evaluation of obesity. Previous thyroid function evaluation suggested CeH [FT4 0.6 ng/mL, thyroid-stimulating hormone (TSH) 2.2 mIU/L] but his physician took no action. At presentation he was clinically and biochemically euthyroid, prepubertal and obese. Serum prolactin (PRL) was undetectable. Biochemistry was normal except for mild hypercholesterolemia, total cholesterol 198 mg/dL. Subsequently FT4 and TSH levels fluctuated between 0.72-0.95 ng/dL (normal 0.8-2.0) and 1.94-5.77 mIU/L (normal 0.3-5.0), respectively. Sequencing of IGSF1 gene revealed a novel genetic change c.3805C>T in exon 19; substitution of amino acid Arginine at position 1269 with a premature «stop» codon resulting in an altered protein product. The patient additionally presented delayed adrenarche, low height velocity that resolved spontaneously and normal pubertal onset associated with increased FSH levels. At 14 years-of-age, while the patient was at Tanner stage 4, PRL levels became detectable, rising gradually to 2.3 ng/mL at last examination. Thyroxine replacement therapy resulted in decrease in total cholesterol 103 mg/dL. A high index of suspicion for the disorder is needed since several measurements of thyroid function may be required for CeH to be disclosed. The patient's normal FT4 levels and normal intelligence would have resulted in a missed diagnosis if the serum PRL levels had not been measured. This case highlights the importance of measuring PRL in a boy with low normal FT4 and normal TSH levels.